2011
DOI: 10.1111/j.1466-7657.2011.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Selecting examinable nursing core competencies: a Delphi project

Abstract: The expert panel met the project aim and provided a set of examinable competencies/activities that they consider will demonstrate the fundamental safety of new registered nurses. The subsequent responsibility for setting up a register for nurses in Indonesia now rests with the Indonesian Ministry of Health. The Indonesian National Nursing Association is working with the Ministry of Health to determine the route and criteria for registration in order to establish a common level of competence for nurses across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The inclusion criteria for experts were: (a) bachelor’s degree or above, (b) senior professional titles, (c) worked for more than 10 years in areas of maternity, NICU, or nursing management, and (d) rich professional knowledge. There is no exact rule for sample size in Delphi study [10,11]; Lock [12] suggested expert panel sizes ranging from 12 to 110. We selected 40 experts who were the nursing directors, NICU medical experts, and nursing specialists in maternity and NICU, respectively, in 4 hospitals in Shandong Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria for experts were: (a) bachelor’s degree or above, (b) senior professional titles, (c) worked for more than 10 years in areas of maternity, NICU, or nursing management, and (d) rich professional knowledge. There is no exact rule for sample size in Delphi study [10,11]; Lock [12] suggested expert panel sizes ranging from 12 to 110. We selected 40 experts who were the nursing directors, NICU medical experts, and nursing specialists in maternity and NICU, respectively, in 4 hospitals in Shandong Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…The majority ruling or a median score as an outcome of the process may be personalized for each study (Humphrey-Murto et al, 2017). Lock (2011) added that the technique should be modified to fit the specific needs of the study especially after multiple iterations.…”
Section: Consensus or Majority Rulingmentioning
confidence: 99%
“…Expert consensus is the most commonly used method for the development of competency standards in health care (Powell, ). The most commonly used formal consensus method in health care is the Delphi method (Byrne, Boon, Austin, Jurgens, & Raman‐Wilms, ; Jorm, ; Lock, ; Vernon, ; Witt & de Almeida, ). This method involves a panel of experts privately rating written statements.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used formal consensus method in health care is the Delphi method (Byrne, Boon, Austin, Jurgens, & Raman-Wilms, 2010;Jorm, 2015;Lock, 2011;Vernon, 2009;Witt & de Almeida, 2008). This method involves a panel of experts privately rating written statements.…”
Section: Introductionmentioning
confidence: 99%